Does an association exist between the hierarchical motor components of upper and lower limbs in stroke?. Issue 3 (July 2016) - Arya, Kamal Narayan; Pandian, Shanta; Kumar, Dharmendra
Summary: Background & objective: Abnormal synergisitic linkage exists between the upper and lower limbs. The relation may persist till the last stage of motor recovery. The objective of the present study was to analyze the relation between the motor components of the upper extremity and lower extremity in stroke subjects. Design: A cross-sectional and correlational design. Setting: Rehabilitation Institute. Participants: Fifty-nine poststroke chronic hemiparetic subjects (39 men; Mean age = 48.81 years; Mean poststroke duration = 11.22 months and 34 right-side paresis). Interventions: Not-applicable. Outcome measures: Fugl-Meyer Assessment (FMA): upper extremity (FMA-UE) and lower extremity (FMA-LE). Results: A moderate positive correlation (r = .65, p < .001) was found between FMA-UE and FMA-LE. FMA-UE (51%) was found to be significantly inferior (p < .001; 95% CI = 6 to 17) in comparison to FMA-LE (63%). Conclusion: In poststroke subjects, there is a moderate positive relation between the recovery components of affected upper limb and lower limb. Stroke rehabilitation should consider hierarchical motor components of the lower limb and upper limb simultaneously.